2017
DOI: 10.1038/jp.2017.10
|View full text |Cite
|
Sign up to set email alerts
|

Sudden versus gradual pressure wean from Nasal CPAP in preterm infants: a randomized controlled trial

Abstract: OBJECTIVE In preterm infants, nasal continuous positive airway pressure (NCPAP) is widely used for treatment of respiratory distress syndrome. However, the strategies for successfully weaning infants off NCPAP are still not well defined and there remains considerable variation between the methods. The objective of this study is to determine whether gradual weaning of NCPAP pressure is more successful than sudden weaning off NCPAP to room air. STUDY DESIGN A randomized controlled trial was conducted in a leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(67 citation statements)
references
References 33 publications
2
62
1
Order By: Relevance
“…The results of this study agree with findings of what to our knowledge is the only other RCT that compares sudden wean and pressure wean in very preterm infants. This study, by Amatya et al, 31 had a sample size of 68 infants born between 26 to 32 weeks of gestation and used successful wean during Abbreviations: IQR, interquartile range; nCPAP, nasal continuous positive airway pressure; NICU, neonatal intensive care unit; PMA, postmenstrual age. a Apgar score at 1 minute was unknown for 4 infants (2%) in the sudden wean group and 7 infants (4%) in the pressure wean group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study agree with findings of what to our knowledge is the only other RCT that compares sudden wean and pressure wean in very preterm infants. This study, by Amatya et al, 31 had a sample size of 68 infants born between 26 to 32 weeks of gestation and used successful wean during Abbreviations: IQR, interquartile range; nCPAP, nasal continuous positive airway pressure; NICU, neonatal intensive care unit; PMA, postmenstrual age. a Apgar score at 1 minute was unknown for 4 infants (2%) in the sudden wean group and 7 infants (4%) in the pressure wean group.…”
Section: Discussionmentioning
confidence: 99%
“…This differs from our results, in which the higher rate of successful weans during the first attempt only applied to infants who were born before 28 weeks of gestation. The study by Amatya et al 31 was not powered to perform a stratified analysis. A successful wean during the first attempt is an outcome that is highly dependent on the readiness and failure criteria used, in particular nCPAP pressure.…”
Section: Discussionmentioning
confidence: 99%
“…We are aware that the latter approach is based on clinical observation and not on data from randomized clinical trials, but we believe that this procedure may reduce the number of patients that fail weaning from CPAP and expedite the course of hospitalization. Currently, to our knowledge, there are no shared recommendations on weaning from CPAP in adults with HRF and severe pneumonia [29], and so far, the majority of evidence on this topic comes from pediatric/neonatal studies [30]. We propose that, as the patient reaches clinical and respiratory stability, the weaning from the helmet should start from reducing the PEEP to the lower possible value (for the helmet, usually 5-6 cmH2O) maintaining a FiO2 not higher than 50%.…”
Section: A Management Algorithm For Covid-19 Patients With De Novo Rementioning
confidence: 99%
“…Between the two general methods, sudden wean has been initially demonstrated to deliver shorter CPAP weaning duration and length of stay in the hospital (Todd et al, 2012). On the contrary, Amatya et al (2017) showed conflicting result in which gradual titration has been more successful in the initial trial but there was no significant difference in the over-all outcomes. However, this could be explained by the difference in the incremental CPAP time off between the two studies.…”
Section: The Role Of Practice Models In Evidence Translationmentioning
confidence: 97%